The influence of Self Efficacy and Locus of Control on employee performance from an Islamic perspective - Hastuti Permana, Putri; Apriana, Agung; Mutiah, Ridla (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research is motivated by the success of an employee's performance being determined by the management who manages it and the employees. Especially in the current era of globalization, competition is increasingly fierce, so employees must be able to contribute to the company's sustainability. The research method used in carrying out this research is a quantitative descriptive research method. The results of this research indicate that companies are expected to continue to improve employee self-efficacy and locus of control and can increase employee job satisfaction. Especially for superiors towards their subordinates, they can provide motivation to subordinates so that they can be motivated to work well and achieve job satisfaction.